The Effect of Time Budget Pressure and Auditor Rotation on Audit Quality with Company Size as A Moderating Variable (An Empirical Study on Non-Banking Financial Sector Companies Listed on the Indonesia Stock Exchange in 2019–2023) - Made Widananda Vira Suksma Paramachintya; Made Yenni Latrini (International Journal of Economics, Management and Accounting, 2025)
Audit quality is defined as the likelihood or probability that an auditor will detect and report any violations or misstatements in a client’s financial statements. This study aims to empirically examine the effect of time budget pressure and auditor rotation on audit quality, with firm size as a moderating variable. The research was conducted on non-bank financial companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The study sample consisted of 50 companies selected using purposive sampling, and the data were analyzed using Moderated Regression Analysis (MRA). The results reveal that time budget pressure and auditor rotation do not have a significant effect on audit quality. Furthermore, firm size does not moderate the relationship between time budget pressure and audit quality, but it does moderate the relationship between auditor rotation and audit quality. These findings underscore the importance of effective time management and auditor rotation policies in maintaining audit quality, particularly for large-scale companies. This study may serve as a useful reference for various stakeholders in understanding the significance of managing time pressure and appropriately implementing auditor rotation to preserve and enhance audit quality.